Aluminum silicon nanoporous material and sewage treatment device
Through the preparation and application of aluminum silicon nano -pores, the problem of cumbersome operation and unstable effects in existing sewage treatment technology has been solved, and the efficient removal of pollutants in sewage is achieved, simple operation and significant effects.
Patent Information
- Application Number
- CN202411611905.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
In the existing wastewater treatment technology, the use of organic flocculants requires real-time adjustment of the concentration, pH value and stirring conditions, which is cumbersome in operation and unstable effect.
The use of aluminum silicon nano -pores, through the formation of gas doping and amproid silicon dioxide shell, the conductive performance and comparison area of the regulatory material is used to form unbalanced potential and external potential in sewage treatment to achieve rapid pollutants. Physical flocculation and precipitation.
The convenience and efficient removal of pollutants in sewage are realized, and the requirements for concentration, pH value and stirring conditions are reduced, and the operation is simple and effective.
Smart Images

Figure CN119161000B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sewage treatment, and in particular to an aluminum silicon nanoporous material and a sewage treatment device. Background Art
[0002] Wastewater treatment is the process of purifying wastewater to meet the water quality requirements for discharge into a water body or reuse. Wastewater treatment is widely used in various fields such as construction, agriculture, transportation, energy, petrochemicals, environmental protection, urban landscape, medical care, and catering.
[0003] Flocculants are often used in sewage treatment. Flocculants are a type of chemical used to remove or reduce turbidity or suspended matter in water, produce large-particle agglomerates, and accelerate the sedimentation rate of impurities and sludge in water. There are two major categories: inorganic and organic flocculants. Inorganic flocculants mainly include aluminum salts and iron salts, such as aluminum sulfate, polyaluminum oxide, ferric chloride and ferrous sulfate. Organic flocculants can be divided into three types according to their charge: anionic, cationic and non-ionic. The main ones are sodium polyacrylate, carboxymethyl cellulose, polyethylene imine, polyethylene oxide, polyacrylamide, etc. Among them, inorganic flocculants have poor flocculation effect when used alone, and generally organic flocculants are used or organic flocculants are used in combination with inorganic flocculants.
[0004] During use, organic flocculants have relatively high requirements for concentration, pH value and stirring conditions, and the concentration and pH value are constantly changing. In actual use, it is necessary to adjust various process parameters in real time according to changes in conditions in order to achieve the best treatment effect. The operation process is relatively cumbersome. Summary of the invention
[0005] In order to achieve convenient and efficient removal of pollutants in sewage, the present application provides an aluminum-silicon nanoporous material and a sewage treatment device.
[0006] In a first aspect, the present application provides an aluminum silicon nanoporous material, which adopts the following technical solution.
[0007] An aluminum silicon nanoporous material, which is composed of an aluminum silicon shell of non-conductive amorphous silicon dioxide and superconducting aluminum silicon nanopores, wherein the specific surface area of the aluminum silicon nanoporous material is 60-70m 2 / g;
[0008] Its preparation method is:
[0009] S1. Preparation of aluminum silicon nanomaterials;
[0010] S2. Vapor phase doping;
[0011] A mixture of titanium tetraacetylacetonate and iron acetylacetonate is used as a precursor gas, and hydrogen is used as a gas carrier to react with aluminum silicon nanomaterials in a CVD reaction chamber; the reaction temperature is 400-500°C, the reaction pressure is 2.5-4.0kPa, the gas flow rate is 200-300ml / min, and the reaction time is 20-30min;
[0012] Annealing treatment after the reaction is completed;
[0013] S3. Formation of amorphous silica shell;
[0014] The gas-phase doped aluminum silicon nanomaterial is dispersed in a sol containing a silicon dioxide precursor, and a silicon dioxide layer is formed on the surface of the material through hydrolysis and condensation reactions. The pH value of the reaction is 3-5, the reaction temperature is 35-45°C, and the reaction time is 30-40h. After the reaction is completed, the aluminum silicon nanoporous material is obtained by centrifugation, washing, drying, and calcination.
[0015] By adopting the above technical scheme, the conductive properties of aluminum silicon nanomaterials are regulated by mixing titanium tetraacetylacetonate and iron acetylacetonate. Titanium tetraacetylacetonate and iron acetylacetonate are heated to a gaseous state and then introduced into a reaction chamber together with a carrier gas (such as nitrogen or argon). On the surface of the aluminum silicon nanomaterial, titanium tetraacetylacetonate decomposes to release titanium atoms, which react with aluminum and silicon atoms in the base material to form titanium-based compounds; acetylacetone and hydrogen react chemically on the surface of the aluminum silicon nanomaterial at high temperature to generate solid substances such as iron oxides or hydroxides, which are deposited on the surface of the material. Then, an amorphous silicon dioxide shell is formed outside the silicon aluminum material to obtain an aluminum silicon nanoporous material.
[0016] Aluminum silicon nano-microporous material is applied to sewage treatment, and unbalanced potential and external field potential are formed on the surface of aluminum silicon nano-microporous material, so that pollutants in sewage are quickly physically flocculated and precipitated. In addition, the aluminum silicon nano-microporous material obtained in this application has a strong adsorption force, which adsorbs ultrafine particulate matter, chromaticity, toxic and harmful substances and odors to the surface of the treatment agent, and quickly flocculates and precipitates and separates from the water body. There are no high requirements for concentration, pH value and stirring conditions during the treatment process. Its excellent adsorption performance and electric field effect make the aluminum silicon nano-microporous material mixed with sewage to achieve the effect of removing pollutants in sewage. Finally, the aluminum silicon nano-microporous material has a huge specific surface area, which can be used as a carrier, and microorganisms reproduce on the huge specific surface area of aluminum silicon to remove pollutants in sewage.
[0017] Furthermore, the specific method of preparing aluminum silicon nanomaterials in S1 is:
[0018] Aluminum sulfate was dissolved to obtain an aluminum sulfate solution, tetrapropylammonium hydroxide was added to the sulfuric acid solution, and the mixture was sealed and stirred for 3 hours to obtain a colorless transparent liquid;
[0019] Then, tetraethyl orthosilicate is added to the colorless transparent liquid to react for 9-10 hours, and then polyethylene glycol is added to obtain a reaction solution;
[0020] The reaction solution is hydrothermally crystallized at 100-120° C. for 24 hours, then cooled to 25-30° C. and filtered to retain the solid. The solid is dried, ground, and calcined to obtain aluminum silicon nanomaterials.
[0021] Furthermore, the weight ratio of the aluminum sulfate to the polyethylene glycol is 1:(25-35).
[0022] By adopting the above technical scheme, a silica-alumina sol precursor is mixed with a polyethylene glycol soft template and hydrothermally treated to prepare aluminum-silicon nanomaterials. The polyethylene glycol plays a structural guiding role, controlling the formation of aluminum-silicon nanomaterial crystals, and obtaining aluminum-silicon nanomaterials with dense and uniform pore structures, which provides a good foundation for the subsequent regulation of conductive properties and the formation of amorphous silica shells.
[0023] Furthermore, in the S2. vapor phase doping, the weight ratio of titanium tetraacetylacetonate to iron acetylacetonate is 1:(1.2-1.5).
[0024] Furthermore, in the S2. gas phase doping, the reaction temperature is 450° C., the reaction pressure is 3.0 kPa, the gas flow rate is 240 ml / min, and the reaction time is 25 min.
[0025] Furthermore, in the formation of the amorphous silica shell, the preparation method of the sol containing the silica precursor is as follows: dissolving tetramethoxysilane in ethanol to obtain a tetramethoxysilane solution with a volume percentage of 5-10%, then adding an acidic catalyst to the tetramethoxysilane solution for hydrolysis, and then adding an alkaline catalyst to obtain a sol containing the silica precursor.
[0026] Furthermore, in the formation of the amorphous silica shell, the ratio of the aluminum silicon nanoporous material and tetramethoxysilane after gas phase doping is 1g of the aluminum silicon nanoporous material to 10ml of tetramethoxysilane.
[0027] Furthermore, in the formation of the amorphous silica shell in S3, the pH value of the reaction for forming a silica layer on the surface of the material through hydrolysis and condensation reaction is 4, the reaction temperature is 40° C., and the reaction time is 35 h.
[0028] By adopting the above technical solution, the formation conditions of the amorphous silica shell are regulated, the thickness and uniformity of the amorphous silica shell are controlled, and an aluminum silicon nano-microporous material with excellent comprehensive performance is obtained.
[0029] In a second aspect, the present application provides a sewage treatment device, which adopts the following technical solution.
[0030] A sewage treatment device comprises a primary treatment device and a secondary treatment device, wherein the secondary treatment device comprises a static pipeline mixer and a sedimentation tank, and sewage and aluminum silicon nanoporous material are mixed in the static pipeline mixer and then enter the sedimentation tank for precipitation.
[0031] Furthermore, the ratio of the aluminum-silicon nanoporous material to sewage is: 0.1-0.15 kg of the aluminum-silicon nanoporous material is added per ton of sewage.
[0032] In summary, this application has the following beneficial effects:
[0033] The conductive properties of aluminum silicon nanomaterials are regulated by mixing titanium tetraacetylacetonate and iron acetylacetonate, and then an amorphous silica shell is formed outside the silicon aluminum material to obtain an aluminum silicon nanoporous material. The aluminum silicon nanoporous material is applied to sewage treatment, and an unbalanced potential and an external field potential are formed on the surface of the aluminum silicon nanoporous material, so that the pollutants in the sewage are quickly physically flocculated and precipitated. In addition, the aluminum silicon nanoporous material obtained in the present application has a strong adsorption capacity, and ultrafine particulate matter, chromaticity, toxic and harmful substances and odors are adsorbed to the surface of the treatment agent, and the ultrafine particulate matter, chromaticity, toxic and harmful substances and odors are quickly flocculated and precipitated and separated from the water body. There are no high requirements for concentration, pH value and stirring conditions during the treatment process. Its excellent adsorption performance and electric field effect enable the aluminum silicon nanoporous material to be mixed with sewage to achieve the effect of removing pollutants in sewage. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a flow chart of the method for preparing aluminum silicon nanoporous material according to Example 1 of the present application;
[0035] Figure 2 It is a structural schematic diagram of the sewage treatment device of the present application;
[0036] Explanation of the reference numerals: 1. Grid tank; 2. Sand settling tank; 3. Static pipeline mixer; 4. Sedimentation tank; 5. Step-by-step filtration tank. DETAILED DESCRIPTION
[0037] The present application is further described in detail below in conjunction with embodiments and drawings.
[0038] raw material
[0039] Titanium tetraacetylacetonate, analytical grade;
[0040] Ferric acetylacetonate, analytical grade;
[0041] Aluminum sulfate, Al 2 (SO 4 ) 3 18H2 O, analytical grade;
[0042] Tetrapropylammonium hydroxide, mass fraction 25%;
[0043] Tetraethyl orthosilicate, analytical grade;
[0044] Polyethylene glycol, analytical grade;
[0045] Tetramethoxysilane, analytical grade;
[0046] Acid catalyst, nitric acid;
[0047] Basic catalyst, triethylamine. Example
[0048] Example 1
[0049] An aluminum silicon nanoporous material, which is composed of an aluminum silicon shell of non-conductive amorphous silicon dioxide and superconducting aluminum silicon nanopores, Figure 1 , and its preparation method is:
[0050] S1. Preparation of aluminum-silicon nanomaterials
[0051] 1) Dissolve 1 kg of aluminum sulfate in 27 L of water to obtain an aluminum sulfate solution, add 45 L of tetrapropylammonium hydroxide to the sulfuric acid solution, seal and stir to react for 3 hours to obtain a colorless transparent liquid;
[0052] 2) adding 36 L of tetraethyl orthosilicate to the colorless transparent liquid obtained in 1) and reacting for 9 h, and then adding 25 kg of polyethylene glycol to obtain a reaction liquid;
[0053] 3) The reaction solution was hydrothermally crystallized at 100°C for 24 hours, then cooled to 25°C and filtered to retain the solids, which were dried and ground, and calcined at 550°C to obtain a white powdery aluminum silicon nanomaterial;
[0054] S2. Vapor phase doping;
[0055] The aluminum silicon nanomaterial obtained in S1 was placed in the CVD reaction chamber, preheated at 300°C for 10 min, and then the temperature in the CVD reaction chamber was raised to 450°C, and the pressure was controlled at 3.0 kPa;
[0056] Then, titanium tetraacetylacetonate and ferric acetylacetonate were mixed in a weight ratio of 1:1.3, and hydrogen was used as a carrier to deliver titanium tetraacetylacetonate and ferric acetylacetonate into a CVD reaction chamber as a precursor gas. The gas flow rate was 240 ml / min, and the precursor gas was deposited on the surface of the aluminum silicon nanomaterial for 25 minutes.
[0057] Annealing treatment after the reaction is completed;
[0058] S3. Formation of amorphous silica shell;
[0059] 1) Preparation of sol containing silica precursor
[0060] 0.8 L of tetramethoxysilane was dissolved in ethanol to obtain a tetramethoxysilane solution with a volume percentage of 8%, and then 1.6 ml of an acidic catalyst was added to the tetramethoxysilane solution for hydrolysis, and then 2.4 ml of an alkaline catalyst was added for stirring and reaction to obtain a sol containing a silicon dioxide precursor;
[0061] 2) Dispersing 0.08 kg S2 of gas-phase doped aluminum silicon nanomaterial in the sol containing silicon dioxide precursor obtained in 1) to form a silicon dioxide layer on the surface of the material through hydrolysis and condensation reaction. The pH value of the reaction is 4, the reaction temperature is 40°C, and the reaction time is 35 hours. After the reaction is completed, centrifugation, washing, drying, and calcination at 550°C are performed to obtain aluminum silicon nanoporous material;
[0062] The specific surface area of the obtained aluminum silicon nanoporous material is 60-70m 2 / g.
[0063] Example 2
[0064] Different from Example 1, the amount of polyethylene glycol added in step S1 in Example 2 is 35 kg.
[0065] Example 3
[0066] Different from Example 1, the amount of polyethylene glycol added in step S1 in 2) of Example 3 is 40 kg.
[0067] Example 4
[0068] Different from Example 1, in Step S2 of Example 4, the weight ratio of titanium tetraacetylacetonate to iron acetylacetonate is 1:1.2.
[0069] Example 5
[0070] Different from Example 1, in Example 5, the weight ratio of titanium tetraacetylacetonate to iron acetylacetonate in step S2 is 1:1.5.
[0071] Example 6
[0072] Different from Example 1, in Example 6, the weight ratio of titanium tetraacetylacetonate to iron acetylacetonate in step S2 is 1.3:1.
[0073] Example 7
[0074] Different from Example 1, in Example 7, in step S2, the reaction temperature is 400° C., the reaction pressure is 4.0 kPa, the gas flow rate is 300 ml / min, and the reaction time is 30 min.
[0075] Example 8
[0076] Different from Example 1, in Example 8, in step S2, the reaction temperature is 500° C., the reaction pressure is 2.5 kPa, the gas flow rate is 200 ml / min, and the reaction time is 20 min.
[0077] Example 9
[0078] Different from Example 1, in Example 9, 0.8 L of tetramethoxysilane was dissolved in ethanol to obtain a tetramethoxysilane solution with a volume percentage of 5%.
[0079] Example 10
[0080] Different from Example 1, in Example 10, 0.8 L of tetramethoxysilane was dissolved in ethanol to obtain a tetramethoxysilane solution with a volume percentage of 10%.
[0081] Embodiment 11
[0082] Different from Example 1, in Example 11, in step S3, the pH value of the reaction is 3, the reaction temperature is 45° C., and the reaction time is 30 h.
[0083] Example 12
[0084] Different from Example 1, in Example 12, in step S3, the pH value of the reaction is 5, the reaction temperature is 35° C., and the reaction time is 40 h.
[0085] Embodiment 13
[0086] Different from Example 1, in Example 13, in step S3, in 2), 0.06 kg of S2 obtained by gas phase doping aluminum silicon nanoporous material is dispersed in the sol containing silicon dioxide precursor obtained in 1).
[0087] Embodiment 14
[0088] Different from Example 1, in Example 14, in step S3, in 2), 0.10 kg of S2 obtained by gas phase doping aluminum silicon nanoporous material is dispersed in the sol containing silicon dioxide precursor obtained in 1).
[0089] Comparative Example
[0090] Comparative Example 1
[0091] The difference from Example 1 is that in Comparative Example 1, an equal amount of titanium tetraacetylacetonate is used to replace iron acetylacetonate.
[0092] Comparative Example 2
[0093] Different from Example 1, in Comparative Example 2, an equal amount of iron acetylacetonate was used to replace titanium tetraacetylacetonate.
[0094] Comparative Example 3
[0095] Different from Example 1, in Comparative Example 3, nitrogen is used as the gas carrier.
[0096] Comparative Example 4
[0097] An aluminum silicon nanoporous material, the preparation method of which is as follows:
[0098] S1. Preparation of aluminum-silicon nanomaterials
[0099] 1) Dissolve 1 kg of aluminum sulfate in 27 L of water to obtain an aluminum sulfate solution, add 45 L of tetrapropylammonium hydroxide to the sulfuric acid solution, seal and stir to react for 3 hours to obtain a colorless transparent liquid;
[0100] 2) adding 36 L of tetraethyl orthosilicate to the colorless transparent liquid obtained in 1) and reacting for 9 h, and then adding 25 kg of polyethylene glycol to obtain a reaction liquid;
[0101] 3) The reaction solution was hydrothermally crystallized at 100°C for 24 hours, then cooled to 25°C and filtered to retain the solids, which were dried and ground, and calcined at 550°C to obtain a white powdery aluminum silicon nanomaterial;
[0102] S2. Vapor phase doping;
[0103] The aluminum silicon nanomaterial obtained in S1 was placed in the CVD reaction chamber, preheated at 300°C for 10 min, and then the temperature in the CVD reaction chamber was raised to 450°C, and the pressure was controlled at 3.0 kPa;
[0104] Then, titanium tetraacetylacetonate and ferric acetylacetonate were mixed in a weight ratio of 1:1.3, and nitrogen was used as a carrier to deliver titanium tetraacetylacetonate and ferric acetylacetonate into a CVD reaction chamber as precursor gas. The gas flow rate was 240 ml / min, and the precursor gas was deposited on the surface of the aluminum silicon nanomaterial for 25 minutes.
[0105] Annealing treatment is performed after the reaction is completed.
[0106] Application Examples
[0107] Application Example 1
[0108] Reference Figure 2A sewage treatment device includes a primary treatment device and a secondary sewage treatment device. The primary sewage treatment device includes a connected grille pool 1 and a grit pool 2. The secondary treatment device includes a static pipeline mixer 3, a sedimentation pool 4 and a step-by-step filtration pool 5. The water inlet of the static pipeline mixer 3 is connected to the water outlet of the grit pool 2, and the water outlet of the static pipeline mixer 3 is connected to the water inlet of the sedimentation pool 4.
[0109] The sewage first passes through the screen pool 1 to intercept some larger garbage, and then enters the grit pool 2. It is left to stand in the grit pool 2 to precipitate some sand and gravel and other materials. The supernatant continues to enter the static pipeline mixer 3. The aluminum silicon nanoporous material obtained in Example 1 is added to the static pipeline mixer 3 and mixed with the sewage, and then enters the sedimentation tank 4. 0.1 kg of aluminum silicon nanoporous material is added to each ton of sewage in the static pipeline mixer 3. The sewage is subjected to sedimentation treatment in the sedimentation tank 4 for 20 minutes, and the supernatant water and sediment are separated. The separated supernatant water enters the step-by-step filtration tank 5 for step-by-step filtration, and then discharged.
[0110] Application Example 2-14
[0111] Different from Application Example 1, the aluminum silicon nanoporous materials in Application Examples 2-14 come from Examples 2-14, respectively.
[0112] Comparative Application Examples
[0113] Comparative Application Examples 1-4
[0114] Different from Application Example 1, the aluminum silicon nanoporous materials in Comparative Application Examples 1-4 come from Comparative Examples 1-4, respectively.
[0115] Performance Testing
[0116] In the application example and the comparative application example, the COD of the sewage is 351 mg / L, the TP is 6.07 mg / L, and the chromium ion content is 0.14 mg / L. The water is taken out to test the COD, TP and chromium ion content, and the removal rates of COD, TP and chromium ions before and after sewage treatment are calculated:
[0117] Removal rate = (COD, TP or chromium ion content of sewage before treatment - COD, TP or chromium ion content of sewage after treatment) / COD, TP or chromium ion content of sewage before treatment × 100%. The results are shown in Table 1.
[0118] Table 1 Performance test results
[0119]
[0120] Combining Application Examples 1-14 with Comparative Application Examples 1-4 and Table 1, it can be seen that the removal rates of COD, TP, and chromium ions in sewage in Application Examples 1-14 are higher than those in Comparative Application Examples 1-4, which shows that the aluminum silicon nanoporous material obtained in the present application has a better sewage treatment effect. This may be because the aluminum silicon nanoporous material obtained in the present application has a strong adsorption force and specific surface area, which adsorbs ultrafine particulate matter, chromaticity, toxic and harmful substances, and odors to the surface of the treatment agent, and an unbalanced potential and an external field potential are formed on the surface of the aluminum silicon nanoporous material, so that the pollutants in the sewage are quickly physically flocculated, precipitated and separated from the water body, achieving a better sewage treatment effect.
[0121] Combining Application Examples 1-3 and Table 1, it can be seen that the removal rate of COD, TP, and chromium ions in sewage in Application Example 2 is the highest, which shows that the amount of polyethylene glycol added when preparing aluminum silicon nanomaterials will affect the sewage treatment effect of the obtained aluminum silicon nanoporous material, among which the ratio in Application Example 2 is better. This may be because in the process of preparing aluminum silicon nanomaterials, the amount of polyethylene glycol plays a structural guiding role, controls the formation of aluminum silicon nanomaterial crystals, and obtains aluminum silicon nanomaterials with dense and uniform pore structures, which provides a good foundation for the subsequent regulation of conductive properties and the formation of amorphous silica shells.
[0122] Combining Application Example 1 with Application Examples 4-6 and Table 1, it can be seen that the removal rates of COD, TP, and chromium ions in sewage in Application Examples 1 and Application Examples 4-5 are higher than those in Application Example 6. This shows that within the ratio range of titanium tetraacetylacetonate and ferric acetylacetonate specified in the present application, the performance of aluminum silicon nanomaterials is regulated by using a mixture of titanium tetraacetylacetonate and ferric acetylacetonate as a precursor gas, and the obtained aluminum silicon nanoporous material has better adsorption and flocculation effects on pollutants, among which the ratio in Application Example 1 is better.
[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An aluminum silicon nanoporous material, characterized in that: It consists of an aluminum silicon shell of non-conductive amorphous silicon dioxide and superconducting aluminum silicon nano-micropores, and the specific surface area of the aluminum silicon nano-micropore material is 60-70m 2 / g; Its preparation method is: S1. Preparation of aluminum silicon nanomaterials; Aluminum sulfate was dissolved to obtain an aluminum sulfate solution, tetrapropylammonium hydroxide was added to the sulfuric acid solution, and the mixture was sealed and stirred for 3 hours to obtain a colorless transparent liquid; Then, tetraethyl orthosilicate is added to the colorless transparent liquid to react for 9-10 hours, and then polyethylene glycol is added to obtain a reaction solution; The reaction solution is hydrothermally crystallized at 100-120° C. for 24 hours, then cooled to 25-30° C. and filtered to retain the solids, which are dried, ground, and calcined to obtain aluminum silicon nanomaterials; S2. Vapor phase doping; A mixture of titanium tetraacetylacetonate and iron acetylacetonate is used as a precursor gas, and hydrogen is used as a gas carrier to react with aluminum silicon nanomaterials in a CVD reaction chamber; the reaction temperature is 400-500°C, the reaction pressure is 2.5-4.0kPa, the gas flow rate is 200-300ml / min, and the reaction time is 20-30min; Annealing treatment after the reaction is completed; S3. Formation of amorphous silica shell; The gas-phase doped aluminum silicon nanomaterial is dispersed in a sol containing a silicon dioxide precursor, and a silicon dioxide layer is formed on the surface of the material through hydrolysis and condensation reactions. The pH value of the reaction is 3-5, the reaction temperature is 35-45°C, and the reaction time is 30-40h. After the reaction is completed, centrifugation, washing, drying, and calcination are performed to obtain the aluminum silicon nanoporous material.
2. The aluminum-silicon nanoporous material according to claim 1, characterized in that: The weight ratio of the aluminum sulfate to the polyethylene glycol is 1:(25-35).
3. The aluminum-silicon nanoporous material according to claim 1, characterized in that: In the S2. vapor phase doping, the weight ratio of titanium tetraacetylacetonate to iron acetylacetonate is 1:(1.2-1.5).
4. The aluminum-silicon nanoporous material according to claim 3, characterized in that: In the S2. gas phase doping, the reaction temperature is 450° C., the reaction pressure is 3.0 kPa, the gas flow rate is 240 ml / min, and the reaction time is 25 min.
5. The aluminum silicon nanoporous material according to claim 1, characterized in that: The S3. In the formation of the amorphous silica shell, the preparation method of the sol containing the silica precursor is: dissolving tetramethoxysilane in ethanol to obtain a tetramethoxysilane solution with a volume percentage of 5-10%, then adding an acidic catalyst to the tetramethoxysilane solution for hydrolysis, and then adding an alkaline catalyst to react to obtain a sol containing the silica precursor.
6. The aluminum-silicon nanoporous material according to claim 5, characterized in that: In the formation of the amorphous silica shell, the ratio of the aluminum silicon nanoporous material and tetramethoxysilane after gas phase doping is 1g of aluminum silicon nanoporous material corresponding to 10ml of tetramethoxysilane.
7. The aluminum-silicon nanoporous material according to claim 6, characterized in that: In the formation of the amorphous silica shell, the pH value of the reaction for forming a silica layer on the surface of the material through hydrolysis and condensation reaction is 4, the reaction temperature is 40° C., and the reaction time is 35 h.
8. A sewage treatment device, characterized in that: It comprises a primary treatment device and a secondary treatment device, wherein the secondary treatment device comprises a static pipeline mixer (3) and a sedimentation tank (4); sewage and the aluminum silicon nanoporous material described in any one of claims 1 to 7 are mixed in the static pipeline mixer (3) and then enter the sedimentation tank (4) for precipitation.
9. A sewage treatment device according to claim 8, characterized in that: The ratio of the aluminum-silicon nanoporous material to sewage is: 0.1-0.15 kg of the aluminum-silicon nanoporous material is added per ton of sewage.
Citation Information
Patent Citations
Core-shell type ZSM-5 molecular sieve and preparation and application thereof
CN104211085A
Core / shell-type micropore / mesoporous composite titanium silicon molecular sieve and preparation method thereof
CN105712367A